Optimizing Telehealth Experience Design Through Usability Testing in Hispanic American and African American Patient Populations: Observational Study - King, D'Arcy (JMIR Rehabil Assist Technol, 2020)
BACKGROUND: Telehealth-delivered pulmonary rehabilitation (telePR) has been shown to be as effective as standard pulmonary rehabilitation (PR) at improving the quality of life in patients living with chronic obstructive pulmonary disease (COPD). However, it is not known how effective telePR may prove to be among low-income, urban Hispanic American and African American patient populations. To address this question, a collaborative team at Northwell Health developed a telePR intervention and assessed its efficacy among low-income Hispanic American and African American patient populations. The telePR intervention system components included an ergonomic recumbent bike, a tablet with a built-in camera, and wireless monitoring devices. OBJECTIVE: The objective of the study was to assess patient adoption and diminish barriers to use by initiating a user-centered design approach, which included usability testing to refine the telePR intervention prior to enrolling patients with COPD into a larger telePR study. METHODS: Usability testing was conducted in two phases to identify opportunities to streamline and improve the patient experience. The first phase included a prefield usability testing phase to evaluate technical, patient safety, and environmental factors comprising the system architecture. This was followed by an ergonomic evaluation of user interactions with the bicycle, telehealth tablets, and connected wearable devices to ensure optimal placement and practical support for all components of the intervention. The second phase of research included feasibility testing to observe and further optimize the system based on iterative rounds of telePR sessions. RESULTS: During usability and feasibility research, we identified and addressed multiple opportunities for system improvements. These included physical and environmental changes, modifications to accommodate individual patient factors, safety improvements, and technology upgrades. Each enrolled patient was subsequently identified and classified into one of the following 3 categories: (1) independent, (2) intermediate, or (3) dependent. This categorization was used to predict the level of training and support needed for successful participation in the telePR sessions. Feasibility results revealed that patients in the dependent category were unable to perform the rehab sessions without in-person support due to low technical acumen and difficulty with certain features of the system, even after modifications had been made. Intermediate and independent users, however, did exhibit increased independent utilization of telePR due to iterative improvements. CONCLUSIONS: Usability testing helped reduce barriers to use for two subsets of our population, the intermediate and independent users. In addition, it identified a third subset, dependent users, for whom the telePR solution was deemed unsuitable without in-person support. The study established the need for the development of standard operating procedures, and guides were created for both patients and remote respiratory therapists to facilitate the appropriate use of the telePR system intervention. Observational research also led to the development of standard protocols for the first and all subsequent telePR sessions. The primary goals in developing standardization protocols were to establish trust, ensure a positive experience, and encourage future patient engagement with telePR sessions.